Electrolyte with good interface contact property and application of electrolyte in sodium-ion battery

By optimizing the proportion of additives and improving the interface kinetics with N-methyl-N-propyl-bisimine and PMMA, a solid electrolyte with high interfacial wetting and good amorphous properties was prepared, which solved the problems of poor interfacial contact and insufficient interfacial wetting in sodium ion batteries, and significantly improved the performance and life of the battery.

CN119852510APending Publication Date: 2025-04-18SUZHOU PUCHANG NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411777006.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The application of existing solid electrolytes in sodium ion batteries is limited by poor interface contact, insufficient wetting and large volume expansion, resulting in high interface resistance and affecting the performance and life of the battery.

Method used

By combining and optimizing the proportion of different additives in the electrolyte, a solid electrolyte with high interfacial wetting and amorphous properties were prepared. The specific steps include using Na3PO4·12H2O, SiO2 and ZrO2 as raw materials, preparing NASICON solid electrolyte through high-temperature solid phase sintering process, and adding N-methyl-N-propyl-bisimine and polymethyl methacrylate (PMMA) to the electrolyte as wetting agent and blended polymer matrix to improve the interface kinetics of the electrolyte.

Benefits of technology

The electrode-electrolyte interface contact and wetting properties in sodium ion batteries are significantly improved, the interface resistance is reduced, and the energy density, cycle life and rate performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an electrolyte with good interface contact performance and application of the electrolyte in a sodium-ion battery, and relates to the technical field of sodium-ion batteries. The method comprises the following specific steps: mixing Na3PO4. 12H2O, SiO2, ZrO2 and absolute ethyl alcohol, carrying out ball milling, and drying to obtain powder; the powder is subjected to sintering, nanocrystallization, spray drying, tabletting, cold isostatic pressing treatment and secondary sintering to form the NASICON solid electrolyte with the monoclinic structure. The electrolyte is soaked in a composite solution containing sodium salt, N-methyl-N-propyl-diimine and PMMA (polymethyl methacrylate), and after the additive fully acts, the diaphragm containing the electrolyte is prepared. According to the method, the overall performance of the sodium-ion battery is integrally improved by using a small amount of additives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an electrolyte with good interface contact and application in sodium ion batteries. Background Art

[0002] Sodium-ion batteries have attracted extensive attention from researchers due to their resource advantages and potential application value in large-scale energy storage systems. Electrolyte is one of the core components of the battery, playing the role of conducting ions and separating the positive and negative electrodes. Currently commonly used organic electrolytes have safety risks such as flammability and leakage, which need to be overcome in the further development and application of sodium-ion batteries. As the core component of all-solid-state batteries, solid-state electrolytes have attracted widespread attention due to their advantages such as non-flammability and high mechanical properties. However, low ionic conductivity, lithium dendrite growth, and solid electrolyte-electrode interface problems limit the practical application of solid-state electrolytes in all-solid-state lithium batteries.

[0003] Solid electrolytes (SSEs) can be used as the best alternative to liquid electrolytes to solve their safety issues due to their high thermal stability and non-flammability. SSEs with high mechanical strength and density can be combined with metal negative electrode materials, making the application of high energy density lithium metal batteries possible. However, the poor contact between rigid SSEs and solid electrodes and the easy side reactions between the electrodes to form new interfacial phases often cause high interfacial resistance problems, which are the main reasons limiting the application of SSEs. In addition, during the charge and discharge process, the volume change of the electrode material can easily lead to the loss of contact between the rigid SSEs and the solid electrodes, which greatly increases the interfacial resistance between the SSEs and the electrodes.

[0004] Polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN) and polymethyl methacrylate (PMMA) are the most common polymer matrices. Among them, PMMA polymer matrix blending helps to improve mechanical and electrical properties. In addition, due to the amorphous nature of PMMA and the strong interaction between the carbonyl side groups in the MMA unit and the carbonates in the liquid electrolyte, the PVDF / HFP / PMMA gel polymer film is conducive to the absorption of the liquid electrolyte, thereby improving the sodium ion conductivity. N-methyl-N-propyl-bisimide is used as a wetting agent to fully contact and wet the electrolyte and electrode surface to significantly improve the interfacial dynamics. Summary of the invention

[0005] The purpose of the present invention is to provide a solid electrolyte with high interface wettability and good amorphism and a method for using it in a sodium ion battery, and to alleviate the disadvantages of poor interface contact between the electrode and the electrolyte, poor wettability and large volume expansion of the sodium ion battery by combining and optimizing the proportions of different additives in the electrolyte.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] An electrolyte with good interface contact and its application in sodium ion batteries, characterized in that the preparation steps are as follows:

[0008] (1) According to weight, 60-80 parts of Na3PO4·12H2O, 120-160 parts of SiO2 and 120-160 parts of ZrO2 are weighed and loaded into a ball mill, 350-450 parts of anhydrous ethanol are added, and ball milling is performed in a heavy-duty horizontal planetary ball mill to uniformly mix the materials. After the ball milling, the ball milling beads and the slurry are separated by a sieve, and the slurry is air-dried to obtain a powder material;

[0009] (2) The powder material in step (1) is placed in a corundum crucible and sintered in a muffle furnace to obtain a NASICON solid electrolyte precursor powder. After mechanical crushing, the powder is ball-milled to nano-size and spray-dried again. The nano precursor powder is pressed into tablets under high pressure, and then cold isostatic pressing is performed to eliminate internal stress and increase the density of the solid electrolyte green body. Finally, the precursor powder is used to bury the green body in a corundum crucible and perform secondary sintering at high temperature to obtain a monoclinic NASICON solid electrolyte.

[0010] (3) Dissolve the sodium salt in a composite solution of N-methyl-N-propyl-bis-imide and polymethyl methacrylate (PMMA), stir the monoclinic NASICON solid electrolyte obtained in step (2) in the mixed solution, then add additives and soak for 8 hours to serve as an electrolyte and a separator.

[0011] In the step (1), the ball milling speed is 180-240 r / min, and the ball milling time is 45-60 mins.

[0012] The blast drying temperature in step (1) is 55-65°C.

[0013] In the step (2), the sintering temperature of the muffle furnace is 1100-1200° C., and the sintering time is 8-10 hours.

[0014] In the step (2), the rotation speed of the nano-milling is 300-350 r / mins.

[0015] In the step (2), the high pressure tableting pressure is 98-100 MPa and the time is 30 seconds.

[0016] In the step (2), the secondary sintering temperature is 1150-1250° C., and the sintering time is 13-16 hours.

[0017] In step (3), the sodium salt is selected from one or a combination of sodium hexafluorophosphate (NaPF6) and sodium perchlorate (NaClO4), and the concentration of the sodium salt is 0.9-1.1M.

[0018] In the step (3), the mass ratio of N-methyl-N-propyl-bisimide to polymethyl methacrylate (PMMA) is 1-7:3-9.

[0019] The amount of the additive added in step (3) is 0.1-2 wt% of the NASICON solid electrolyte, and the preparation method is:

[0020] By weight, 10-20 parts of hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.003-0.03 parts of 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 2-5 parts of potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; and 3-6 parts of sulfuric acid are mixed in 200-430 parts of toluene, and reacted at a temperature range of 90 to 100° C. for 150-200 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0021] Preparation mechanism of the above additives: Carboxyl-hydroxyl esterification reaction: The carboxyl group (-COOH) in hexa(4-'carboxyphenoxy')cyclotriphosphazene undergoes a condensation reaction with the hydroxyl group (-OH) in 8-hydroxyquinoline copper salt or trifluoro(2-hydroxyphenyl)borate potassium. This reaction forms an ester bond by eliminating water molecules, connecting the two molecules to obtain a new, larger molecular structure.

[0022] The above additives: 1. Optimize the electrode / electrolyte interface: The improved cyclotriphosphazene compound can improve the compatibility of the electrolyte with the sodium electrode, optimize the transport kinetics of sodium ions, and reduce the performance degradation of the battery during the cycle. In particular, increasing the conductivity of the electrolyte and improving the quality of the SEI film directly affect the energy density, cycle life and rate performance of the battery. 2. Effectively optimize the electrode / electrolyte interface: The improved cyclotriphosphazene compound can improve the compatibility of the electrolyte with the sodium electrode, optimize the transport kinetics of sodium ions, and reduce the performance degradation of the battery during the cycle. In particular, increasing the conductivity of the electrolyte and improving the quality of the SEI film directly affect the energy density, cycle life and rate performance of the battery.

[0023] Technical mechanism of the above scheme:

[0024] The present invention provides a solid electrolyte method with high interface wettability and good amorphous property. First, PMMA polymer matrix blending contributes to the improvement of mechanical properties and electrical properties. In addition, due to the amorphous characteristics of PMMA and the strong interaction between the carbonyl side groups in the MMA unit and the carbonate in the liquid electrolyte. Secondly, N-methyl-N-propyl-bisimide is used as a wetting agent. This is because a small amount of liquid components are introduced into the solid electrolyte, and the interface of the electrolyte is deeply modified to form a wettable interface layer, so that the electrolyte and the electrode surface are fully contacted and infiltrated to significantly improve the interface dynamics. Thereby providing high electrode-electrolyte interface chemical and mechanical stability. Therefore, the combination of N-methyl-N-propyl-bisimide that inhibits the poor wetting of the electrolyte-electrode interface and polymethyl methacrylate (PMMA) that improves the poor amorphous property of the solid electrolyte can effectively inhibit the defects of the solid electrolyte during the charge and discharge process.

[0025] Technical effects:

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention provides a method for inhibiting gas production during the charge and discharge process of a sodium ion battery. A solid electrolyte method with high interface wettability and good amorphousness is used. First, the PMMA polymer matrix blending helps to improve the mechanical and electrical properties. In addition, due to the amorphous characteristics of PMMA and the strong interaction between the carbonyl side groups in the MMA unit and the carbonates in the liquid electrolyte. Secondly, N-methyl-N-propyl-bisimide is used as a wetting agent to fully contact and wet the electrolyte and electrode surfaces to significantly improve the interface dynamics. Thereby providing high electrode-electrolyte interface chemical and mechanical stability. Therefore, the combination of N-methyl-N-propyl-bisimide, which inhibits the poor wettability of the electrolyte-electrode interface, and polymethyl methacrylate (PMMA), which improves the poor amorphousness of the solid electrolyte, can effectively inhibit the defects of the solid electrolyte during the charge and discharge process.

[0028] (2) The preparation process provided by the present invention is relatively simple, the dosage is small, and the overall performance of the sodium ion battery is improved with a small amount of additives. The product performance is relatively good and has certain competitive advantages. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of application of the present invention. Without departing from the spirit and essence of the present invention, modifications or replacements made to the inventive method, steps or conditions all belong to the scope of the present invention.

[0030] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0031] Example 1

[0032] This embodiment provides a method for a solid electrolyte with high interface wettability and good amorphousness, comprising the following components:

[0033] (1) Using Na3PO4·12H2O, SiO2, and ZrO2 as raw materials, the optimal sintering temperature and sintering time for preparing NASICON solid electrolyte by high-temperature solid phase sintering process are 1200℃ and 15h, respectively. 12 Weigh 200g of the raw materials corresponding to the product into a ball mill, add 300mL of alcohol, and grind on a heavy-duty horizontal planetary ball mill at 200r min -1 The ball mill was performed at a speed of 60 minutes to achieve a uniform mixing effect. The ball mill was taken out and the ball mill beads and slurry were separated using a sieve. The obtained slurry was dried at 60°C for 12 hours.

[0034] (2) Collect the dried powder material and place it in a corundum crucible. Use a muffle furnace to sinter it at 1100°C for 10 h to obtain NASICON solid electrolyte precursor powder. After mechanical crushing, heat it at 300 r min. -1 The nano-sized particles were ball-milled at a speed of 1000 rpm and spray-dried again. Some of the nano-precursor powder was taken out and pressed at 98 MPa for 30 seconds to form a sheet, and then cold isostatic pressing was performed to eliminate internal stress and increase the density of the solid electrolyte green body. Finally, the green body was buried in a corundum crucible with the precursor powder and sintered twice at 1200 ° C for 15 hours to obtain a monoclinic NASICON solid electrolyte.

[0035] (3) NaClO4 was dissolved in a composite solution of N-methyl-N-propyl-bis-imide and polymethyl methacrylate (PMMA) in a mass ratio of 1:1, and the sodium salt concentration was 1 M.

[0036] (4) The monoclinic NASICON solid electrolyte obtained in step (2) is stirred uniformly in the mixed solution, and then additives are added and fully immersed for 8 hours to form an electrolyte and a separator.

[0037] The additive is added in an amount of 0.1wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0038] 10g hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.003g 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 2g potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; 3g sulfuric acid are mixed in 200g toluene and reacted at 90°C for 150 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0039] Example 2

[0040] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0041] The mass ratio of N-methyl-N-propyl-bis-imide and polymethyl methacrylate (PMMA) is 1:9;

[0042] The additive is added in an amount of 0.3wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0043] 10g hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.003g 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 2g potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; 3g sulfuric acid are mixed in 200g toluene and reacted at 90°C for 150 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0044] Example 3

[0045] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0046] The mass ratio of N-methyl-N-propyl-bis-imide to polymethyl methacrylate (PMMA) is 2:8.

[0047] The additive is added in an amount of 0.6 wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0048] 10g hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.003g 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 2g potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; 3g sulfuric acid are mixed in 200g toluene and reacted at 90°C for 150 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0049] Example 4

[0050] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0051] The mass ratio of N-methyl-N-propyl-bis-imide to polymethyl methacrylate (PMMA) is 3:7.

[0052] The additive is added in an amount of 0.9wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0053] 15g of hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.015g of 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 3.5g of potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; and 4.5g of sulfuric acid are mixed in 315g of toluene and reacted at a temperature range of 95°C for 175 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0054] Example 5

[0055] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0056] The mass ratio of N-methyl-N-propyl-bis-imide to polymethyl methacrylate (PMMA) is 4:6.

[0057] The additive is added in an amount of 1.2 wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0058] 15g of hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.015g of 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 3.5g of potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; and 4.5g of sulfuric acid are mixed in 315g of toluene and reacted at a temperature range of 95°C for 175 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0059] Example 6

[0060] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0061] The mass ratio of N-methyl-N-propyl-bis-imide to polymethyl methacrylate (PMMA) is 6:4.

[0062] The additive is added in an amount of 1.4 wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0063] 15g of hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.015g of 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 3.5g of potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; and 4.5g of sulfuric acid are mixed in 315g of toluene and reacted at a temperature range of 95°C for 175 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0064] Example 7

[0065] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0066] The mass ratio of N-methyl-N-propyl-bis-imide to polymethyl methacrylate (PMMA) is 7:3.

[0067] The additive is added in an amount of 1.6 wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0068] 20g of hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.03g of 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 5g of potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; and 6g of sulfuric acid are mixed in 430g of toluene and reacted at a temperature range of 100°C for 200 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0069] Example 8

[0070] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0071] The mass ratio of N-methyl-N-propyl-bis-imide to polymethyl methacrylate (PMMA) is 8:2.

[0072] The additive is added in an amount of 1.8 wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0073] 20g of hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.03g of 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 5g of potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; and 6g of sulfuric acid are mixed in 430g of toluene and reacted at a temperature range of 100°C for 200 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0074] Example 9

[0075] This embodiment prepares a solid electrolyte with high interface wettability and good amorphousness, which is different from the embodiment 1 in that:

[0076] The mass ratio of N-methyl-N-propyl-bis-imide to polymethyl methacrylate (PMMA) is 9:1.

[0077] The additive is added in an amount of 2wt% of the NASICON solid electrolyte, and the preparation method is as follows:

[0078] 20g of hexa(4-'carboxyphenoxy')cyclotriphosphazene, CAS No. 69322-61-8; 0.03g of 8-hydroxyquinoline copper salt, CAS: 13014-03-4; 5g of potassium trifluoro(2-hydroxyphenyl)borate, CAS: 850313-92-7; and 6g of sulfuric acid are mixed in 430g of toluene and reacted at a temperature range of 100°C for 200 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.

[0079] Comparative Example 1

[0080] (1) Using Na3PO4·12H2O, SiO2, and ZrO2 as raw materials, the optimal sintering temperature and sintering time for preparing NASICON solid electrolyte by high-temperature solid phase sintering process are 1200℃ and 15h, respectively. 12 Weigh 200g of the raw materials corresponding to the product into a ball mill, add 300mL of alcohol, and grind on a heavy-duty horizontal planetary ball mill at 200r min -1 The ball mill was performed at a speed of 60 minutes to achieve a uniform mixing effect. The ball mill was taken out and the ball mill beads and slurry were separated using a sieve. The obtained slurry was dried at 60°C for 12 hours.

[0081] (2) Collect the dried powder material and place it in a corundum crucible. Use a muffle furnace to sinter it at 1100°C for 10 h to obtain NASICON solid electrolyte precursor powder. After mechanical crushing, heat it at 300 r min. -1 The nano-sized particles were ball-milled at a speed of 1000 rpm and spray-dried again. Some of the nano-precursor powder was taken out and pressed at 98 MPa for 30 seconds to form a sheet, and then cold isostatic pressing was performed to eliminate internal stress and increase the density of the solid electrolyte green body. Finally, the green body was buried in a corundum crucible with the precursor powder and sintered twice at 1200 ° C for 15 hours to obtain a monoclinic NASICON solid electrolyte.

[0082] Comparative Example 2

[0083] (1) Using Na3PO4·12H2O, SiO2, and ZrO2 as raw materials, the optimal sintering temperature and sintering time for preparing NASICON solid electrolyte by high-temperature solid phase sintering process are 1200℃ and 15h, respectively. 12 Weigh 200g of the raw materials corresponding to the product into a ball mill, add 300mL of alcohol, and grind on a heavy-duty horizontal planetary ball mill at 200r min -1 The ball mill was performed at a speed of 60 minutes to achieve a uniform mixing effect. The ball mill was taken out and the ball mill beads and slurry were separated using a sieve. The obtained slurry was dried at 60°C for 12 hours.

[0084] (2) Collect the dried powder material and place it in a corundum crucible. Use a muffle furnace to sinter it at 1100°C for 10 h to obtain NASICON solid electrolyte precursor powder. After mechanical crushing, heat it at 300 r min. -1 The nano-sized particles were ball-milled at a speed of 1000 rpm and spray-dried again. Some of the nano-precursor powder was taken out and pressed at 98 MPa for 30 seconds to form a sheet, and then cold isostatic pressing was performed to eliminate internal stress and increase the density of the solid electrolyte green body. Finally, the green body was buried in a corundum crucible with the precursor powder and sintered twice at 1200 ° C for 15 hours to obtain a monoclinic NASICON solid electrolyte.

[0085] (3) The NASICON solid electrolyte is fully immersed in N-methyl-N-propyl-bisimide wetting agent for later use.

[0086] Test Example 1: Electrochemical Performance Test

[0087] Battery assembly: The positive electrode materials of the embodiment and the comparative example are Na3V2(PO4)3-Na, the conductive material is CNT, and the binder is PVDF; they are weighed according to a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is added to make a viscous uniform black slurry. It is coated on aluminum foil and baked in a vacuum drying oven at 120°C for 12 hours to obtain a positive electrode sheet. It is sliced ​​using a button battery slicer to obtain a circular positive electrode sheet.

[0088] The Na3V2(PO4)3-Na battery was tested in the voltage range of 2.0V-4.2V, first discharged at a rate of 0.1C, then discharged at 0.01C to a voltage of 2.0V, and then charged at 0.1C to 4.2V.

[0089] Test results:

[0090]

[0091] Through the above specific implementation methods and test results, it can be seen that the method can improve the overall performance of sodium ion batteries with a relatively small amount of additives, and the effect is significant.

[0092] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the existing technology should be within the scope of protection determined by the claims.

Claims

1. An electrolyte with good interface contact and its application in sodium ion battery, characterized in that: The preparation steps are as follows: (1) According to weight, 60-80 parts of Na3PO4·12H2O, 120-160 parts of SiO2 and 120-160 parts of ZrO2 are weighed and loaded into a ball mill, 350-450 parts of anhydrous ethanol are added, and ball milling is performed in a heavy-duty horizontal planetary ball mill to uniformly mix the materials. After the ball milling, the ball milling beads and the slurry are separated by a sieve, and the slurry is air-dried to obtain a powder material; (2) The powder material in step (1) is placed in a corundum crucible and sintered in a muffle furnace to obtain a NASICON solid electrolyte precursor powder. After mechanical crushing, the powder is ball-milled to nano-size and spray-dried again. The nano precursor powder is pressed into tablets under high pressure, and then cold isostatic pressing is performed to eliminate internal stress and increase the density of the solid electrolyte green body. Finally, the precursor powder is used to bury the green body in a corundum crucible and perform secondary sintering at high temperature to obtain a monoclinic NASICON solid electrolyte. (3) Dissolve the sodium salt in a composite solution of N-methyl-N-propyl-bis-imide and polymethyl methacrylate (PMMA), stir the monoclinic NASICON solid electrolyte obtained in step (2) in the mixed solution, then add additives and soak for 8 hours to serve as an electrolyte and a separator.

2. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: In the step (1), the ball milling speed is 180-240 r / min, and the ball milling time is 45-60 mins.

3. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: The blast drying temperature in step (1) is 55-65°C.

4. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: In the step (2), the sintering temperature of the muffle furnace is 1100-1200° C., and the sintering time is 8-10 hours.

5. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: In the step (2), the rotation speed of the nano-milling is 300-350 r / mins.

6. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: In the step (2), the high pressure tableting pressure is 98-100 MPa and the time is 30 seconds.

7. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: In the step (2), the secondary sintering temperature is 1150-1250° C., and the sintering time is 13-16 hours.

8. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: In step (3), the sodium salt is selected from one or a combination of sodium hexafluorophosphate (NaPF6) and sodium perchlorate (NaClO4), and the concentration of the sodium salt is 0.9-1.1M.

9. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: In the step (3), the mass ratio of N-methyl-N-propyl-bisimide to polymethyl methacrylate (PMMA) is 1-7:3-9.

10. The electrolyte with good interface contact and its application in sodium ion battery according to claim 1, characterized in that: The amount of the additive added in step (3) is 0.1-2 wt% of the NASICON solid electrolyte, and the preparation method is: By weight, 10-20 parts of hexa(4-'carboxyphenoxy')cyclotriphosphazene, 0.003-0.03 parts of 8-hydroxyquinoline copper salt, 2-5 parts of potassium trifluoro(2-hydroxyphenyl)borate, and 3-6 parts of sulfuric acid are mixed in 200-430 parts of toluene, and reacted at a temperature range of 90 to 100° C. for 150-200 minutes; after the reaction is completed, the toluene is removed by reduced pressure distillation to obtain an additive.